Life table and population parameter of Sogatella furcifera (Horvath) (Homoptera:Delphacidae) in rice. - Win, S.S.; Muhamad Awang, Rita; Mior Ahmad, Zainal Abidin; Adam, Nur Azura (American Network for Scientific Information, 2009)
Survivorship and fertility of the White Backed Plant Hopper (WBPH), Sogatella furcifera were assessed under laboratory conditions in Myanmar. A pair of five days old WBPH was released into a wooden cage covered with wire mesh sieve. Thirty days old rice plant in a pot was placed on the floor of the wooden cage. The single sex method was applied in the life table study. Life tables and population parameters were constructed based on unlimited food supply and a natural enemies-free environment. Results showed that the highest mortality occurred in the immature stages, especially in the first and second instars. The life table analysis showed that population densities of S. furcifera decreased gradually. The proportion of male to female observed was 1:0.88. The females could live for a maximum of 12 days. The trend of oviposition showed a peak at about the 10th day of the female life span. The mean number of eggs produced per female was 8.75. The intrinsic rate of increase (rm) was 0.06999 per female per day and daily finite of increase (λ) was 1.0255 per female per day, with a mean generation time (T) of 34.97 days. The net reproductive rate (Ro) of the population was 9.2732. The population Doubling Time (DT) was within 10.88 days. It could be concluded that the survivorship curve reflected a modest rate of mortality during the early life stages and a gradual reduction when approaching adulthood. All the surviving nymphs underwent four moults. The life table showed that about 37.26% of S. furcifera eggs successfully emerged as adults and high mortality occurred during the early immature stages. This type of survivorship is commonly classified as type II.